Geomechanical properties of gas hydrate-bearing sediments in Shenhu Area of the South China Sea. (November 2021) - Wei, Jiangong; Yang, Lin; Liang, Qianyong; Liang, Jinqiang; Lu, Jingan; Zhang, Wei; Zhang, Xuhui; Lu, Xiaobing
Abstract: It is essential to understand the in-situ geomechanical properties of natural gas hydrate-bearing reservoirs for hydrate drilling, the design of reservoir stimulation and production schemes, geologic disaster prevention, and environmental impact assessment. In this way, it serves as the basis for the development and utilization of gas hydrate resources. In 2016, the Guangzhou Marine Geological Survey conducted the fourth natural gas hydrate drilling (Expedition GMGS4) in the north of the South China Sea, during which the effective stress of gas hydrate-bearing reservoirs in the study area was ascertained and gas hydrate-bearing pressure cores were collected. The effective stress was determined to be 700–800 kPa by in-situ piezocone penetration tests. The saturation, permeability, and shear strength of gas hydrates in the pressure core samples were measured under the in-situ stress state using the shipboard multi-sensor core logger (MSCL), pressure core analysis and transfer system (PCATS), and PCATS Triaxial system. Based on this, the distribution characteristics and the relationship of the permeability and gas hydrate saturation of the gas hydrate-bearing reservoirs were explored. Furthermore, the effects of effective stress and gas hydrate saturation on shear strength of gas hydrate-bearing clayey-silt sediments were mainly analyzed, as well as the stress–strain characteristics of gas hydrate-bearing sediments. The results are as follows: (i) the gas hydrate saturation and reservoir permeability in the study area are 0.7%–55% and 10 −3 –10 −1 mD, respectively, indicating low-permeability reservoirs; (ii) the gas hydrate saturation and reservoir permeability have obvious anisotropy in horizontal and vertical directions; (iii) the undrained shear strength of gas hydrate-bearing sediments is 0.24–0.52 MPa, and the shear strength of fine-grained sediments is more sensitive to the changes of in-situ stress. In the case that deviatoric stress continues increasing, micro-fractures may occur inside gas hydrate-bearing sediments, and this can lead to drastic changes in the strength of gas hydrate-bearing reservoirs. Therefore, it is necessary to take into account the effects of micro-fractures in gas hydrate-bearing reservoirs on engineering safety during long-term hydrate production. Highlights: The in-situ effective stress of the hydrate-bearing reservoirs was obtained. Hydrate saturation and reservoirs permeability have obvious anisotropy. The permeability reduction index was determined to be 2.2–4.5 in the study area. The shear strength of the hydrate-bearing reservoirs is 0.24–0.52 MPa.